A Study on BCR-ABL Kinase Domain Mutations in Chronic Myeloid Leukemia from Western India - Gadhia, Pankaj; Jeejan, Jessica; Shah, Vishma; Patel, Monika; Vaniawala, Salil (Asian Pacific Journal of Cancer Biology, 2021)
Background: BCR-ABL kinase domain(KD) mutations accounts for 60-80% of Imatinib resistance in chronic myeloid leukemia (CML) – chronic phase (CP). Patients with CML who are receiving imatinib treatment, a mutation analysis is required to find out the resistance of imatinib as per European Leukemia Net (ELN) criteria. The present study was carried out to assess for different types of mutations responsible for resistance of imatinib treatment from Western India. Methods: In a retrospective study, the patients who were tested for imatinib resistance were analysed for IRMA testing using direct sequencing of BCR-ABL transcript by Sanger method. Results: A total of 215 patients were tested for Imatinib resistance analysis (IRMA), of which 45 (20.93%) had detectable mutations. The highest frequency of mutation recorded at T315I amino acids site, followed by M244V and G250E sites. Conclusion: The patients who were tested for IRMA showed 20.93 % positive mutations with reference to its resistance are discussed.